2019
DOI: 10.1111/obr.12828
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible factor 1‐alpha (HIF‐1α) as a factor mediating the relationship between obesity and heart failure with preserved ejection fraction

Abstract: Summary Heart failure with preserved ejection fraction (HFpEF), a common condition with an increased mortality, is strongly associated with obesity and the metabolic syndrome. The latter two conditions are associated with increased epicardial fat that can extend into the heart. This review advances the proposition that hypoxia‐inhibitory factor‐1α (HIF‐1α) maybe a key factor producing HFpEF. HIF‐1α, a highly conserved transcription factor that plays a key role in tissue response to hypoxia, is increased in adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 143 publications
(290 reference statements)
2
48
0
1
Order By: Relevance
“…The 67 genes downstream of TFs with significantly higher expression in the mNIA diet compared with the NIA diet were also significantly overrepresented in the PI3K/Akt pathway (9 genes, FDR = 0.002). Increased HIF-1 expression is associated with upregulation of collagen isoforms and TIMPs in the heart, leading to increased fibrosis (51). The PI3K/ Akt pathway plays a key role in cardiac hypertrophy regulation of cardiac titin, stiffness, and angiogenesis (52).…”
Section: Resultsmentioning
confidence: 99%
“…The 67 genes downstream of TFs with significantly higher expression in the mNIA diet compared with the NIA diet were also significantly overrepresented in the PI3K/Akt pathway (9 genes, FDR = 0.002). Increased HIF-1 expression is associated with upregulation of collagen isoforms and TIMPs in the heart, leading to increased fibrosis (51). The PI3K/ Akt pathway plays a key role in cardiac hypertrophy regulation of cardiac titin, stiffness, and angiogenesis (52).…”
Section: Resultsmentioning
confidence: 99%
“…Impaired glucose metabolism, increased lipid accumulation and ROS levels might cause hypoxia and chronic pathological expression level of HIF-1α in the heart ( Warbrick and Rabkin, 2019 ; Movafagh et al., 2015 ). Chronic activation of HIF-1α was responsible for recruiting M1 macrophages in the heart and mediated metabolic inflammation in cardiomyocytes, thereby releasing IL-6, MCP-1, TNF-α, and IL-1β; NADPH oxidase; and connective tissue growth factor; the resulting chronic inflammation accelerated cardiac fibrosis and impaired the cardiac diastolic function ( Warbrick and Rabkin, 2019 ) ( Warbrick and Rabkin, 2019 ). Recently, research found that knock out of HIF-1α protected HF in the animal model ( Kumar et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired glucose metabolism, increased lipid accumulation and ROS levels might cause hypoxia and chronic pathological expression level of HIF-1α in the heart (43) (44). Chronic activation of HIF-1α was responsible for recruiting M1 macrophages in the heart and mediated metabolic in ammation in cardiomyocytes, thereby releasing IL-6, MCP-1, TNF-α, and IL-1β, NADPH oxidase, and connective tissue growth factor; the resulting chronic in ammation accelerated cardiac brosis and impaired the cardiac diastolic function (43) (45). Recently, research found that knockout of HIF-1α protected HF in the animal model (9).…”
Section: Discussionmentioning
confidence: 99%